Activation of AMP-activated Protein Kinase Is Essential for Lysophosphatidic Acid-induced Cell Migration in Ovarian Cancer Cells - Kim, Eung-Kyun (American Society for Biochemistry and Molecular Biology, 2011)
Lysophosphatidic acid (LPA) is a bioactive phospholipid that affects various biological functions, such as cell proliferation, migration, and survival, through LPA receptors. Among them, the motility of cancer cells is an especially important activity for invasion and metastasis. Recently, AMP-activated protein kinase (AMPK), an energy-sensing kinase, was shown to regulate cell migration. However, the specific role of AMPK in cancer cell migration is unknown. The present study investigated whether LPA could induce AMPK activation and whether this process was associated with cell migration in ovarian cancer cells. We found that LPA led to a striking increase in AMPK phosphorylation in pathways involving the phospholipase C-β3 (PLC-β3) and calcium/calmodulin-dependent protein kinase kinase β (CaMKKβ) in SKOV3 ovarian cancer cells. siRNA-mediated knockdown of AMPKα1, PLC-β3, or (CaMKKβ) impaired the stimulatory effects of LPA on cell migration. Furthermore, we found that knockdown of AMPKα1 abrogated LPA-induced activation of the small GTPase RhoA and ezrin/radixin/moesin proteins regulating membrane dynamics as membrane-cytoskeleton linkers. In ovarian cancer xenograft models, knockdown of AMPK significantly decreased peritoneal dissemination and lung metastasis. Taken together, our results suggest that activation of AMPK by LPA induces cell migration through the signaling pathway to cytoskeletal dynamics and increases tumor metastasis in ovarian cancer.